2013
DOI: 10.1167/iovs.12-11221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Factors on the Proliferation and Gene Expression of Human Meibomian Gland Epithelial Cells

Abstract: PURPOSE. We hypothesize that growth factors, including epidermal growth factor (EGF) and bovine pituitary extract (BPE), induce proliferation, but not differentiation (e.g., lipid accumulation), of human meibomian gland epithelial cells. We also hypothesize that these actions involve a significant upregulation of genes linked to cell cycle processes, and a significant downregulation of genes associated with differentiation. Our objective was to test these hypotheses.METHODS. Immortalized human meibomian gland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Immortalized human meibomian gland epithelial cells (Liu et al 2010) were cultured in the presence or absence of 10% fetal bovine serum, according to published techniques (Liu et al 2013). After reaching 80 to 90% confluence (∼ 5 × 10/ 6 well), cells were exposed to the vehicle (0.02% ethanol) or azithromycin (10 μg/ml; Santa Cruz Biotechnology, TX) for 5 days and then processed for histological and biochemical procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Immortalized human meibomian gland epithelial cells (Liu et al 2010) were cultured in the presence or absence of 10% fetal bovine serum, according to published techniques (Liu et al 2013). After reaching 80 to 90% confluence (∼ 5 × 10/ 6 well), cells were exposed to the vehicle (0.02% ethanol) or azithromycin (10 μg/ml; Santa Cruz Biotechnology, TX) for 5 days and then processed for histological and biochemical procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The notable differences between 2D format and 3D culture in CK1 expression and cell appearances could raise the important hypothesis that HMGECs may function as ductal epithelial cells rather than acinar cells as long as they are cultured in a 2D format regardless of serum treatment. Liu et al 20 reported that HMGECs exhibited lower cell proliferation and keratinization when cultured with serum-containing medium. 20 In particular, CK6 gene expression was significantly downregulated when…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 20 reported that HMGECs exhibited lower cell proliferation and keratinization when cultured with serum-containing medium. 20 In particular, CK6 gene expression was significantly downregulated when…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Cells were treated with ethanol vehicle, 10 lg/mL AZM (Santa Cruz Biotechnology, Dallas, TX, USA), 10 nM IGF-1 (National Hormone and Peptide Program, Torrance, CA, USA), or a combination of 10 lg/mL AZM and 10 nM IGF-1 for 5 to 13 days.…”
Section: Methodsmentioning
confidence: 99%